#TITLE_ALTERNATIVE# - TRIMULIADI SURYANA (NIM : 15007124) ; Pembimbing : Dhemi Harlan, ST., MT., M.Sc.,Ph.D, YUDHA
Handling floods disaster needs to be done effectively and efficiently according to the area’s problem’s charateristics that were reviewed, since not all problems can be solved with the same solution, as is the case in the Northern Coastal Jakarta. A gravity system, which is used in drainage system, cannot overcome the flood disasters that occured because the elevation of channel water is lower than the elevation of the sea on average. Therefore, another solution to overcome this problem is by using a polder integrated system in the area around the channel. Polder system usually applied at the low-lying areas that have lower water channel elevation than the sea elevation. In polder system, water flowed with the help of a pump that works on the upstream river that flowing the water into the sea, in order to maintain the water’s debit in the channel. Polder system planning in the research’s location uses the hidrology and hydraulics basis theories. Hidrology theory used includes the analysis of rainfall, rainfall frequency analysis, and ITB Unit-1 Hidrogaf method plan’s debit analysis. Hydraulics theory used includes the basic flow equation, momentum equation, the equation of conservation energy that applied in numerical channel’s model. The numerical modelling done by two programs, HEC-RAS and MIKE-11. The results from the programming modelling will be used as the basis for determining the pump capacity that will be used in upstream river. The location for this study is in Ciliwung-Gunung Sahari river, around Hailai- Jakarta Utara. The data that used in this study includes rainfall’s data in three stations from 1998 to 2008. The modelling results is in form of open channel model with the total pump capacity 60 m3/s in the end of downstream part channel.